2019
DOI: 10.1021/acsbiomaterials.9b01012
|View full text |Cite
|
Sign up to set email alerts
|

PLG Bridge Implantation in Chronic SCI Promotes Axonal Elongation and Myelination

Abstract: One million estimated cases of spinal cord injury (SCI) have been reported in the United States and repairing an injury has constituted a difficult clinical challenge. The complex, dynamic, inhibitory microenvironment post injury, which is characterized by pro-inflammatory signaling from invading leukocytes and lack of sufficient factors that promote axonal survival and elongation, limits regeneration. Herein, we investigated the delivery of polycistronic vectors, which have the potential to co-express factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Poly-lactide-co-glycolide (PLG) is one of the most frequently used synthetic biomaterials for drug delivery, due to its controlled and sustained release properties, low toxicity, and biocompatibility with tissue and cells [ 46 , 47 ]. PLG has been widely used as a material for spinal cord repair or peripheral nerve conduits [ 47 ].…”
Section: Delivery Of Ntfs’ and Associated Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly-lactide-co-glycolide (PLG) is one of the most frequently used synthetic biomaterials for drug delivery, due to its controlled and sustained release properties, low toxicity, and biocompatibility with tissue and cells [ 46 , 47 ]. PLG has been widely used as a material for spinal cord repair or peripheral nerve conduits [ 47 ].…”
Section: Delivery Of Ntfs’ and Associated Challengesmentioning
confidence: 99%
“…NTFs regulate the development and survival of neurons, and they appear to be involved in the endogenous neuroprotection of different neurons. Several studies have reported that NTFs, particularly glial cell-derived neurotrophic factor (GDNF), ciliary neurotrophic factor (CNTF), brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), neurotrophin-3 (NT-3), and neurotrophin-4/5 (NT-4/5), act regeneratively in different animal models [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] and patients [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ,…”
Section: Introductionmentioning
confidence: 99%
“…[ 177 ] Alternatively, single axons have been reported to align well with features on the order of 1 µm [ 178,179 ] and bundles of spinal cord axons regenerate robustly through guidance tubes on the order of 100's of µm. [ 180–182 ]…”
Section: Biomaterials Design Considerationsmentioning
confidence: 99%
“…[ 365,367 ] Similar guidance conduits have been explored for their ability to facilitate axon regeneration across spinal cord lesions and as carriers for transplanted NS/PCs that direct their maturation. [ 180,181,366 ] Multilayered, tubular structures have been typically made by either stacking multiple films or nanofiber mats that are then rolled together [ 337 ] or electrospinning layers directly onto a cylinder. [ 365,366 ] Qian et al created layered, tubular scaffolds in which the innermost layer consisted of polydopamine and arginylglycylaspartic acid (RGD), followed by two layers of a PCL/graphene film, and an outermost layer of polydopamine and RGD.…”
Section: Composite Materials For Interfacing With Neural Cellsmentioning
confidence: 99%
See 1 more Smart Citation